Digital literacy for the development of social skills in teacher training students (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
Digital literacy is proposed for the development of social skills in teacher training students. Under the positivist paradigm, quantitative approach, descriptive type, non-experimental, cross-sectional, field design. The population consisted of 41 students and one teacher from the sixth semester of the Formative Research Programs 1 and 2, Semester, in Early Childhood Education, University of Pamplona, Cread Cúcuta. The technique used was a survey, with a questionnaire containing 39 items on a Likert scale, concluding that the teacher and students effectively use technologies and develop social skills, but that the students have shortcomings in intrapersonal relationships.